The Influence of Merdeka Curriculum Implementation and Teacher Motivation on Student Academic Achievement in Rural Indonesian Senior High Schools - Rasyid Siddik; Bukman Lian; Mahasir Mahasir (Journal of Social Work and Science Education, 2027)
This quantitative correlational study examined the influence of curriculum implementation and teacher motivation on student academic achievement at SMA Negeri 1 Semendawai Barat, South Sumatra, Indonesia, during the implementation of the Merdeka Curriculum. Data were collected from 41 teachers and principals using validated Likert-scale questionnaires (Cronbach's α = 0.982 for curriculum, 0.942 for motivation, 0.927 for achievement) and documented academic records. Multiple regression analysis revealed that curriculum implementation significantly predicted student achievement (β = 0.824, p < 0.001), explaining 67.9% of the variance. Teacher motivation also demonstrated significant predictive power (β = 0.742, p < 0.001). Simultaneously, both variables accounted for 76.9% of the variance in student academic achievement (F = 100.086, p < 0.001). These findings highlight that curriculum reform effectiveness depends on motivated teachers who can translate policy into meaningful classroom practice. The study contributes empirical evidence from an under-researched rural Indonesian context and offers practical implications for curriculum leadership, teacher professional development, and instructional supervision in similar settings. School improvement efforts should integrate curriculum strengthening with teacher motivation strategies rather than addressing them separately.